2016
DOI: 10.1021/acschembio.5b01039
|View full text |Cite
|
Sign up to set email alerts
|

A Bacterial Cell Shape-Determining Inhibitor

Abstract: Helicobacter pylori and Campylobacter jejuni are human pathogens and causative agents of gastric ulcers/cancer and gastroenteritis, respectively. Recent studies have uncovered a series of proteases that are responsible for maintaining the helical shape of these organisms. The H. pylori metalloprotease Csd4, and its C. jejuni homologue Pgp1, cleave the amide bond between meso-diaminopimelate and iso-d-glutamic acid in truncated peptidoglycan side chains. Deletion of either csd4 or pgp1 results in bacteria with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…These targets are broad-spectrum in the sense that endo- and carboxypeptidases are common throughout the bacterial kingdom5657, but many PG peptidases are redundant5859 and therefore detrimental effects might be compensated in other species and it may also be possible to design narrow-spectrum options that specifically target Pgp1 or Pgp2. Intriguingly, Liu et al 60. recently reported a bacterial cell shape-determining inhibitor of H. pylori Csd4 (homologue of Pgp1 in C. jejuni ) that causes significant cell straightening of H. pylori and a diminished, yet observable, effect on the morphology of C. jejuni .…”
Section: Resultsmentioning
confidence: 99%
“…These targets are broad-spectrum in the sense that endo- and carboxypeptidases are common throughout the bacterial kingdom5657, but many PG peptidases are redundant5859 and therefore detrimental effects might be compensated in other species and it may also be possible to design narrow-spectrum options that specifically target Pgp1 or Pgp2. Intriguingly, Liu et al 60. recently reported a bacterial cell shape-determining inhibitor of H. pylori Csd4 (homologue of Pgp1 in C. jejuni ) that causes significant cell straightening of H. pylori and a diminished, yet observable, effect on the morphology of C. jejuni .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study described the synthesis of a phosphinic acid-based inhibitor against Csd4 from H . pylori [ 60 ]. It demonstrated that the hydrophilic small-molecule inhibitor of Csd4 can cross the outer membrane of H .…”
Section: Discussionmentioning
confidence: 99%
“…One of the ways to reduce the pathogenicity of H. pylori is the possibility of disrupting helical cell formation. An example of a substance with such properties is a phosphonic acid-based pseudopeptide, which has the ability to bind to the active site of Csd4 (or Pgp1 in Campylobacter jejuni ) and mediate protein activity disturbances [ 89 ]. The millimolar concentrations of this compound contributed to the straightening of H. pylori and C. jejuni cells.…”
Section: Peptidoglycan Deacetylase Pgda and Acetyltransferase Patamentioning
confidence: 99%